BRAND ASSET VALUATOR (BAV) ACHETYPES: PENTINGNYA KESELARASAN WARNA DAN KEPRIBADIAN MEREK DALAM WEB DESIGN - Natarina Setyaningrum (Kompetensi (Competence : Journal of Management Studies), 2015)
Technology is growing rapidly, the number of website also increase from year to year. Color is one of the important aspect in marketing, but some people not understand the important of color theory. Colorin web design can affect consumers on how they look a brand personality. Theory Young and Rubicam tell about Brand Asset Valuator (BAV) Archetypes. This valuator measures how good is a brand personality. BAV Archetypes devided in two characteristic, good and shadow. This research, examine about how important color harmony and brand personality in web design.